Sky location of Galactic white dwarf binaries in space-based gravitational wave detection - Pan Guo; Hong-Bo Jin; Cong-Feng Qiao; Yue-Liang Wu (Results in Physics, 2024)
Quickly localizing the identified white dwarf (WD) binaries is the basic requirement for the space-based gravitational wave (GW) detection. In fact, the amplitude of GW signals are modulated by the periodic motion of GW detectors on the solar orbit. The intensity of the observed signals is enhanced according to the observation time beyond a year to enhance a high signal to noise ratio (SNR). As data gap exists, the completeness of the data observed for a long time depends on filling gaps in the data. Actually, in a year period, the GW sources have a best observation orbit position of GW detectors, where the intensity of GW is maximum. Thus, the best positions can be searched for the verified GW sources of the sky map to enhance SNR too, which avoids filling data gaps. For the three arms response intensity of the GW signals changing more clearly with the location of the GW sources relative to the detector, the noises and the suppression of noise by time delay interferometer are ignored. As a verification case, the four WD binaries are chosen, whose best observation orbit positions of the GW detectors are related to the direction of WD binaries perpendicular to the detection arms. The two verification binaries: J0806 and V407 Vul are observed at the best orbit positions by TAIJI for the short time of 2 and 3 days respectively. The corresponding intensities of GWs are above the values of the TAIJI sensitivity curve, significantly. Location parameter estimation of the verification WD binaries are performed using the Metropolis–Hastings MCMC method. The confidence level of the parameters obtained in the best position is significantly several times higher than that in the worst position where the direction of WD binaries are almost parallel to the detection arms. Compared with a single detector, the network of two detectors improve slightly the accuracy of location of the verification binaries. These results imply that the searching of GW signals and parameter estimation of GW sources from the experimental data of the space-based mission do not ignore the orbit positions relevant to GW sources.